Posterior Pericardial Window Technique to Prevent PostoperativePericardial Effusion in Cardiac Surgery - (:unkn) unknown (My University, 2019)
ABSTRACTINTRODUCTION: The aim was to determine the effectiveness of the posterior pericardial window (PW) technique in preventing the development of pericardial effusion (PE) following coronary artery bypass grafting surgery (CABG).METHODS: Patients undergoing coronary surgery were randomly divided into a control or a PW group. We divided 220 patients randomly into 2 groups, the posterior pericardial window group (n=110) and the control group (n=110). Preoperative, intraoperative and postoperative clinical data were collected retrospectively, including incidence of pericardial tamponade, drainage volume, ventilation time andmoderate to large pericardial effusion. Evaluations were completed preoperatively, before discharge, and on postoperative 7 and 30 days including electrocardiography,chest radiography, echocardiography. Postoperative causes of morbidity, the duration of intensive care unit and hospital stay were recorded.RESULTS: There was no significant difference in demographic data between two groups (P>.05). Echocardiography evaluations revealed no significant difference between groups preoperatively; however, before discharge the control group had a significantly higher number of patients with early and late cardiac tamponade comparedwith the PW group (P<.05). The incidence of postoperative pleural effusion in the PW group was significantly higher than control group. New onset atrial fibrillation was significantly more common in control subjects than in the PW group (P <.05).DISCUSSION and CONCLUSION: Posterior pericardial window technique is a safe and effective method which is easy to perform without any serious complication. This procedure may reduce late cardiac tamponade events and effusion-relatedatrial fibrillation which may be a fatal complication in CABG patients

ÖZ GİRİŞ ve AMAÇ: Posterior perikardiyal pencere tekniğinin, koroner arter bypass greftleme (CABG) ameliyatı sonrası perikardiyal efüzyon gelişimini önlemedeki etkinliğini belirlemekti. YÖNTEM ve GEREÇLER: Koroner cerrahi geçirecek hastalar rastgele bir kontrole veya perikardiyal pencere tekniği grubuna ayrıldı. Toplamda 210 hastayı 2 gruba ayırdık, posterior perikardiyal pencere grubu (n = 110) ve kontrol grubu (n = 110). Preoperatif, intraoperatif ve postoperatif klinik veriler retrospektif olarak toplandı. Preoperatif, taburcu olmadan önce ve postoperatif 7. ve 30. günlerde yapılan değerlendirmelere elektrokardiyografi, göğüs radyografisi, ekokardiyografik incelemeler yapıldı. Postoperatif morbidite nedenleri ve yoğun bakım ünitesinde ve hastanede kalış süreleri kaydedildi. BULGULAR: İki grup arasında demografik veriler açısından anlamlı fark yoktu (P >.05). Ekokardiyografi incelemeleri ameliyat öncesi gruplar arasında anlamlı bir farklılık yoktu; bununla birlikte, taburcu edilmeden önce, kontrol grubunda, perikardiyal pencere grubuna kıyasla, erken ve geç kardiyak tamponad anlamlı olarak yüksek bulundu (P <.05). Perikardiyal pencere grubunda postoperatif plevral efüzyon insidansı kontrol grubundan anlamlı olarak yüksek olarak tespit edildi. Yeni başlangıçlı atriyal fibrilasyon, kontrollerde perikardiyal pencere grubundan anlamlı olarak daha yaygındı (P <.05). TARTIŞMA ve SONUÇ: Posterior perikardiyal pencere tekniği, ciddi komplikasyonlar olmadan kolay uygulanabilir ve güvenli bir yöntemdir. Bu prosedür, geç kardiyak tamponadı ve CABG hastalarında ölümcül bir komplikasyon olabilen efüzyonla ilişkili atriyal fibrilasyonu azaltabilir.
Kalp Cerrahisinde Postoperatif Perikardiyal Efüzyonun Önlenmesi İçin Posterior Perikardiyal Pencere Tekniği